Treatment expectations and goals among patients with chronic myeloid leukemia in Germany: a patient-centered perspective - Ernst, Philipp; Lohse, Cera; Lauseker, Michael; Geißler, Jan; le Coutre, Philipp; Brümmendorf, Tim Henrik; Saußele, Susanne; Burchert, Andreas; Franke, Georg-Nikolaus; La Rosée, Paul; Brioli, Annamaria; Schenk, Thomas; et al. (Leukemia, 2026)
Chronic myeloid leukemia (CML) is a chronic condition with excellent long-term survival under tyrosine kinase inhibitor (TKI) therapy. However, patient priorities regarding treatment goals and quality of life remain insufficiently understood. We conducted a nationwide online survey among German CML patients in collaboration with the German CML Alliance and patient organizations to assess treatment goals at diagnosis, during therapy, and in the treatment-free remission phase. The questionnaire included validated measures of treatment satisfaction, fear of progression, and quality-of-life priorities, supplemented by newly developed items. Between November 2024 and February 2025, 582 patients (median age 56 years, 48.8% female) completed the survey. Overall TKI tolerability was rated positively (median 4/5), particularly in first-line therapy and among patients with shorter disease duration, whereas long-term survivors reported more daily-life limitations. Younger patients ( < 45 years) emphasized fertility, sexuality, and work-related concerns, while older patients prioritized tolerability, independence, and mental health. Treatment history shaped expectations: those with discontinuation experience were more willing to accept adverse effects for the prospect of remission. Overall, patient priorities diverged between achieving deep molecular response and maintaining optimal tolerability. Integrating patient-reported preferences into shared decision-making may enhance satisfaction, adherence, and long-term outcomes of patients with CML.
Online veröffentlicht: 19. Dezember 2025
Gesehen am 05.02.2026